EXPLORING STUDENTS’ READING INTEREST DURING COVID-19 PANDEMIC - Annisa Aulya Rahimah; Istiqomah Istiqomah; Pika Sulistiorini; Tryana Arianti Putri; Amayra Tannoubi (Universitas Sriwijaya, 2022)
The objective of this study, which is being conducted in the middle of the COVID-19 outbreak, was to explore children's interest in reading. The investigation was conducted at the University of Indonesian Antasari in Banjarmasin, more precisely within the English Education Study Program context. The quantitative approach was applied with a survey design, and the participants were made up of 39 students who were enrolled in the second, fourth, and sixth semesters respectively. The items on the questionnaire were used to gather data, which was then subjected to descriptive analysis. The outcomes of this study indicate that the vast majority of respondents like reading when they are doing their academics at home. The kind of reading that is often regarded as being the most delightful is one in which the reader engages in the process of reading fiction using traditional reading tools. According to the study results that were carried out, the amount of time that students who attended lessons at home spent reading daily varied anywhere from fifteen minutes to more than an hour. According to the findings of this research, professors should present lecture materials so that students will be interested in reading them for certain academics. Additionally, students should make it a habit to read to cultivate their perceptiveness, knowledge, and innovative thinking.